1991
DOI: 10.1093/ejo/13.2.134
|View full text |Cite
|
Sign up to set email alerts
|

Dental and skeletal changes following sagittal split osteotomy for correction of mandibular prognathism

Abstract: Skeletal and dental changes were examined in 15 patients presenting with a Class III malocclusion treated by a sagittal split osteotomy. All patients received orthodontic treatment with Straightwire appliances both prior to and following surgery. These appliances were also used for fixation. The lower incisors were proclined by 8.4 degrees before surgery with little change in upper incisor inclination. With surgery, there was a mean reduction of 4.3 degrees in the angle SNB. Following surgery, the relapse in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…Because of the uprighting of lower anterior teeth after decompensation, the reverse overjet was increased. That means the occlusal relationship and profile appearance will be even worse after decompensation, which increases the present discrepancy [22]. This has been proved in this study and it is necessary to explain this phenomenon to patients before treatment.…”
Section: Investigation Of the Incisor Inclination And Arch Width Chansupporting
confidence: 56%
“…Because of the uprighting of lower anterior teeth after decompensation, the reverse overjet was increased. That means the occlusal relationship and profile appearance will be even worse after decompensation, which increases the present discrepancy [22]. This has been proved in this study and it is necessary to explain this phenomenon to patients before treatment.…”
Section: Investigation Of the Incisor Inclination And Arch Width Chansupporting
confidence: 56%
“…The superimposition method applied here 14 is different from other studies that have used coordinates 16,17 and partial structures for registration 18 . By using the entire cranial base as a reference, both the inclination and position in three planes of space are corrected.…”
Section: Discussionmentioning
confidence: 99%
“…Decompensation of the lower incisors with combined surgical and orthodontic Class III treatment has been reported to occur with variable success. 10,12,16,21,23,40 Some investigators have observed that lower incisors remain retroclined at the end of treatment, 12,40 others have reported successful pre-surgical decompensation, followed by 'round-tripping' back to the original compensated positions. 10,23 In addition, others have shown that lower incisor pre-surgical decompensation can be maintained until the completion of appliance treatment, which is consistent with the current findings.…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…12 A number of authors have attempted to provide specific cephalometric guidelines regarding the most appropriate treatment plan for any given patient. 8,[13][14][15][16] While some treatment effects of orthodontic camouflage [17][18][19][20] and orthognathic surgery 12,[21][22][23] have been documented in the literature, only rarely have these two methods been directly compared. 10,16 Therefore, the present study was undertaken to evaluate differences in pre-and post-treatment characteristics of a group of Class III patients treated with either contemporary orthodontic camouflage or orthognathic surgery, and to compare the range of skeletal, dental and soft tissue changes that are likely to occur as a result of treatment, with a particular reference to the influence of premolar extractions on the resultant incisor positions and angulations.…”
Section: Introductionmentioning
confidence: 99%